(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
The diagonosis of drowning is one of the most difficult in forensic pathology. Drowning is substantiated as a cause of death when the types of diatoms in human organs matches diatoms present in the putative drowning medium. Water bodies which are having microscopic unicellular algae called diatoms in varying percentages serve as an important evidence for medicolegal officers to give their final opinion about a cause of death of a body recovered in or near a waterbody.